Computed tomography based modelling of the behaviour of closed cell metallic foams using a shell approximation. (September 2020) - Ghazi, A.; Berke, P.; Tiago, C.; Massart, T.J.
Abstract: This study presents an imaged-based shell modelling strategy for closed cell metallic foams exploiting X-ray Computed Tomography scans, with its illustration on ALCORAS® foams. Based on an in situ X-ray CT compression test, the 3D segmentation is complemented by a watershed method and a geodesic reconstruction technique to isolate cells and to identify missing walls. An implicit 3D geometry is reconstructed for each cell based on a distance field computation technique. An automated procedure extracts a shell geometry from this implicit 3D geometry, followed by a finite element meshing step. The resulting FE model is solved using ABAQUS/Explicit with an elasto-plastic-damage constitutive model for the cell walls behaviour, and with consideration of contacts between cell walls. A comparison of the simulation results is conducted with experimental force-displacement curves and scanned deformed configurations. The deformation and failure mechanisms under quasi-static compression are investigated numerically and compared with the result of the in-situ experimental measurement. The simulation is shown to predict the yield zones on both the macroscopic and cell levels. A combination of correlated microstructural morphological features (cell size, cell wall thickness, surrounding cells) is identified as critical in deformation and failure mechanisms. Graphical abstract: Unlabelled Image Highlights: An automated methodology extracts a shell FE model from CT images for closed cell foams. A characterization of the cell scale structure of ALCORAS® foam is performed. Simulation and experimental results are compared for a foam compression test. CT scans and simulations are used to compare mesoscale deformation and failure mechanisms.